Food Safety: Does Your Kitchen Pass the Test? - Linda B. Bobroff; Jennifer Hillan (EDIS)
Older adults are at increased risk for foodborne illness. To help reduce your risk, follow safe food handling practices at home. How does your kitchen measure up? This 3-page fact sheet was written by Linda B. Bobroff and Jennifer Hillan and published by the UF Department of Family Youth and Community Sciences, October 2013.